The Effects of Product Quality, Service Quality, and Price on Customer Satisfaction - Batu Bara, Citra Maulani; Suryadi, Nanang (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The rapid growth of the culinary industry in Indonesia has driven business actors to continuously improve quality in order to remain competitive and retain customers. Mie Gacoan, as one of the fast-food brands currently popular among the public particularly in Malang City, faces challenges in maintaining customer satisfaction amidst intense competition. This study aims to examine the influence of product quality, service quality, and price on customer satisfaction at Mie Gacoan in Malang. A quantitative approach was employed using an explanatory research design. The population consisted of Mie Gacoan customers in Malang City, and the sample was selected through non-probability purposive sampling, totaling 220 respondents. Data were collected via an online questionnaire using Google Forms and analyzed through multiple linear regression with the help of SPSS version 25. The results show that all three independent variables significantly affect customer satisfaction simultaneously, with an F- value of 26.408 and a significance level of 0.000. Individually, product quality has a coefficient of 0.213 (p = .000), service quality 0.072 (p = .030), and price 0.190 (p = .044). The adjusted R² value of 0.258 indicates that these variables explain 25.8% of the variation in customer satisfaction. The novelty of this study lies in the simultaneous application of the three variables to a fast-growing local brand that has not been widely examined in previous academic studies. The findings provide strategic insights for Mie Gacoan’s management and other culinary businesses to improve service quality and pricing strategies in order to enhance customer satisfaction.